Controlling for presentation effects in choice - Yves Breitmoser (Quantitative Economics, 2021)
Experimenters make theoretically irrelevant decisions concerning user interfaces and ordering or labeling of options. Reanalyzing dictator games, I first show that such decisions may drastically affect comparative statics and cause results to appear contradictory across experiments. This obstructs model testing, preference analyses, and policy predictions. I then propose a simple model of choice incorporating both presentation effects and stochastic errors, and test the model by reanalyzing the dictator game experiments. Controlling for presentation effects, preference estimates become consistent across experiments and predictive out-of-sample. This highlights both the necessity and the possibility to control for presentation in economic experiments.
Keywords: C10; C90; 330; counterfactual predictions; laboratory experiment; Presentation effects; utility estimation